AKTUALISASI PENDIDIKAN KARAKTER DALAM PROSES PEMBELAJARAN MATA KULIAH UMUM (MKU) DI UNIVERSITAS NEGERI SEMARANG - Sunarto, Sunarto; Suhardiyanto, Andi (Jurnal Penelitian Pendidikan, 2013)
This study aims to identify the extent to which aspects of character education has been actualized in a learning General Courses, what barriers are perceived by the lecturer of General Courses, and how expectations of faculty and students associated with the custodian of the learning process as a vehicle for character education General Courses . Based on the research results and the discussion above, the conclusions generated in this study, among others. (1) Lectures General Courses with learning components in it has been actualized values of character education. General Courses learning as character education makes it different from the other subjects of learning where learning competencies expected of General Courses not just mastery of the learning material or purely cognitive aspects, but more important than that is the process of internalization of the self-learning participants. Lecturers and students alike expect General Courses displays learning materials are more than just what is contained in textbooks, but also coupled with current issues in society and the emotional touches that are awakening to the students to realize the values instilled character it is in real life.